Pengaruh Investasi Terhadap Penyerapan Tenaga Kerja dan Pertumbuhan Ekonomi di Provinsi Sulawesi Selatan - Fauzan, Ahmad; Rahman, Abdul (ICOR: Journal of Regional Economics, 2022)
Economic growth is very important in any economic system adopted by a region. One that can be a driver or a barrier to economic growth in an area is the available workforce in that area. In an effort to absorb the workforce, it is necessary to carry out what is called investment. This study was conducted with the aim of analyzing the effect of domestic and foreign investment on economic growth through employment in South Sulawesi Province. This type of research is quantitative with the research location is South Sulawesi. Using secondary time-series data obtained from BPS, SIMREG BAPPENAS, and other sources with the method of collection is documentation. This study concludes that domestic investment has an indirect effect on economic growth through employment in South Sulawesi Province. However, both domestic investment and employment do not have a direct influence on economic growth in South Sulawesi Province. Foreign investment has an indirect influence on economic growth through employment in South Sulawesi Province. However, for the direct effect, only foreign investment has a positive and significant effect on economic growth in South Sulawesi Province. Keyword: Economic Growth, Workforce, And Investment